MINERALS AND TYPE 2 DIABETES MELLITUS –LEVEL OF ZINC, MAGNESIUM AND CHROMIUM IN DIABETIC AND NON DIABETIC POPULATION - Huma Yahya; K.M. Yahya (Journal of University Medical & Dental College, 1970)
ABSTRACT Back ground: Minerals play a vital role in metabolic pathways in human body. For example Zn plays a key role in the synthesis and action of insulin, both physiologically and in the pathologic state of diabetes. Objective: To see the levels of zinc in diabetic and non diabetic patients attending Aziz Fatimah Hospital (AFTH) in Faisalabad. Patients and methods: Thirty test subjects with type 2 diabetes mellitus and thirty non diabetes mellitus were selected randomly from out patients department (OPD) of AFTH. Primary end point was to see the level of zinc. We also screened them for levels of magnesium and chromium. Patients were also stratified to low, middle and high socio economic status. Five millilitre blood sample was collected from each subject for the analysis of above mentioned elements. One millilitre serum was drawn from blood sample for wet digestion. Sample was diluted up to 50 ml by using de-ionized water. Digested sample was analyzed by atomic absorption spectrophotometer for minerals. Statistical analysis was done by using analysis of variance (ANOVA). Results: Serum zinc levels were significantly lower in diabetic subjects than non diabetics (p<0.05). Zinc levels ranged from 1.05-4.8 mg/dl in males and 1.7-3.5 mg/dl in females of middle socioeconomic group which was very low than normal non-diabetic population. Mg and chromium was also very low. Conclusion: Zinc levels are very low in diabetic than normal which may affect their diabetic control. Same is the case with Mg and Cr.